The role of asymmetry and uncertainties in the capital flows- Economic Growth Nexus - Ibrahim Dolapo Raheem; Sara Le Roux; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
This study examines the asymmetry between capital flows and economic growth in 42 countries for the period 1990-2017. It further argues that uncertainty is an important channel through which asymmetry operates. As such, the three measures of uncertainty are macroeconomic, fiscal and institutional. The Generalised Method of Moments is used as an empirical strategy. The existence of an asymmetry is confirmed by the findings as capital flows are more reactive to economic drag when compared to economic growth. Furthermore, the channels through which asymmetry operate are heterogeneous to measures of capital flows and proxies for uncertainty.
Keywords: C13; F3; G15; O16; 330; Capital flows; Economic growth; Asymmetry; Uncertainty and Emergingcountries